2022
DOI: 10.1162/rest_a_01272
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Retail E-Commerce on Relative Prices and Consumer Welfare

Abstract: This paper examines the impact of retail e-commerce on pricing behavior and welfare. Using Japanese data, we find that e-commerce lowered relative inflation rates for goods sold intensively online. We use long time series and historical catalog sales as an instrument for e-commerce sales intensity. The entry of e-commerce firms raised the rate of intercity price convergence in physical stores for goods sold intensively online, but not for other goods, which suggests e-commerce enhances price arbitrage. We esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The decrease in price is consistent with Jo et al (2019), which reveals that e-commerce decreases prices and increases consumer welfare. The interaction term (ExportRatio j × Post t ) is used to address the endogeneity concern.…”
Section: Baseline Resultssupporting
confidence: 77%
“…The decrease in price is consistent with Jo et al (2019), which reveals that e-commerce decreases prices and increases consumer welfare. The interaction term (ExportRatio j × Post t ) is used to address the endogeneity concern.…”
Section: Baseline Resultssupporting
confidence: 77%
“…Some studies showed that e-commerce could reduce consumption inequality, because its positive effect on consumption was stronger for residents in small and remote cities or rural areas (Fan et al, 2018;Couture et al, 2021). The potential increase in product variety in rural areas, the decline in price, and the positive income effect resulting from employment or entrepreneurial opportunities created by e-commerce are the main mechanisms by which e-commerce has contributed to the reduction of consumption inequality (Fan et al, 2018;Jo et al, 2019;Luo and Niu, 2019;Couture et al, 2021). Huang et al (2018) found that e-commerce fueled entrepreneurship by alleviating financial constraints and moderated the reliance of household entrepreneurship on social networks.…”
Section: E-commerce and Consumption Inequalitymentioning
confidence: 99%
“…The benchmark regressions may have certain endogeneity issues resulting from reverse causality and unobserved omitted variables. To address the endogeneity problems, referring to Nunn and Qian (2014) and Jo et al (2019), we adopted the interaction terms of the number of post offi ces in 2004 at the provincial level and the lagged online household expenditure as the IV and used the 2SLS method. The development of e-commerce is inseparable from the development of express delivery, so regions with a higher number of post offices historically are presumed to have experienced better e-commerce development.…”
Section: Endogeneity Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar vein, with the increasing availability of online data, it has become possible to examine the role, or lack thereof, of Internet frictions and price dispersion. While some studies document relatively high levels of uniform pricing in online markets, particularly as online transparency or competition intensify (Brown & Goolsbee, 2002;Cavallo, 2017Cavallo, , 2019Ater & Rigbi, 2023;Jo et al, 2022;Aparicio Rigobon, 2023), it is clear that price dispersion still exists online, especially across sellers (Brynjolfsson & Smith, 2000;Baylis & Perloff, 2002;Chevalier & Goolsbee, 2003;Baye et al, 2004;Orlov, 2011;Overby & Forman, 2015;Gorodnichenko & Talavera, 2017;Gorodnichenko et al, 2018;Cavallo, 2019;González & Miles-Touya, 2018).…”
Section: Related Literaturementioning
confidence: 99%